Sunday

April 19, 2015

April 19, 2015

Posted by **amelia** on Saturday, October 24, 2009 at 1:54pm.

- algebra -
**Reiny**, Saturday, October 24, 2009 at 2:00pmLet 2^x = y

then your equation becomes

2y^2 - 5y + 2 = 0

(2y-1)(y-2) = 0

y = 1/2 or y = 2

then 2^x = 1/2 --- x = -1

or

2^x = 2 --- x = 1

Math - We have an important chemsitry test due and I want to make sure that I do...

Intermediate Algebra - Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x...

algebra - Solve the indicated variable: 1. Volume of a cone: solve for h: V=Ļir^...

Algebra - Solve for x: h=(k/4)(x-3L) Solve for B: v-6Bxk=7B Solve for S: z+(1/7)...

Algebra - Hi, how would I solve these 2 equations using algebra? It states in ...

Algebra 2 - Solve each system 3x+2y= -2 9x- y= -6 I know how to solve for x but ...

Algebra 2 - How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of...

algebra - solve for the indicated variable: a. temperature formula solve for F: ...

Algebra - FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x...

algebra - im trying to solve a literal equation, then solve the specific ...